Historical context - Ewart, Gordon (Scottish Archaeological Internet Reports, 2001)
The abbey was founded in 1142 by Fergus, Lord of Galloway as a daughter house of Rievaulx in north Yorkshire. The success of the abbey as the earliest and wealthiest Cistercian foundation in the region was not maintained into the later 13th century. An indication of the mixed fortunes of the abbey during the 13th century survives in the form of petitions to the English Crown. The history of subsequent years is largely obscure. By the mid 16th century the community of brethren was relatively small, numbering a single prior and nine monks in 1545.